The regulatory network of lncRNA DLX6-AS1/miR-149–5p/ERP44 is possibly related to the progression of preeclampsia. (April 2020) - Liu, Ronghui; Wang, Xiaolu; Yan, Qian
Abstract: Background: Long noncoding RNA DLX6 antisense RNA 1 (DLX6-AS1) has been reported to be involved in various human diseases, however, its potential role in the pathogenesis of preeclampsia (PE) has not been fully explored. Methods: The levels of DLX6-AS1, microRNA-149–5p (miR-149–5p) and endoplasmic reticulum protein 44 (ERP44) were measured by quantitative real-time polymerase chain reaction (qRT-PCR). Some clinicopathological parameters of PE were statistically analyzed. The cell proliferation, invasion and angiogenesis were assessed by methylthiazolyldiphenyl-tetrazolium bromide (MTT), transwell and tube formation assays, respectively. Levels of all protein were detected by western blot. The target relationship was predicted by StarBase v2.0 and confirmed by dual-luciferase reporter assay. Results: Higher levels of DLX6-AS1 and ERP44, lower level of miR-149–5p were observed in PE placenta tissues. Compared with PE group with low DLX6-AS1 expression, the systolic blood pressure, diastolic blood pressure and proteinuria levels in the group with high DLX6-AS1 expression were higher, and the infant body weight level was lower. The role of miR-149–5p on these clinicopathological parameters of PE patients was opposite to that of DLX6-AS1, while ERP44 had the same effect as DLX6-AS1. Besides, DLX6-AS1 directly targeted miR-149–5p and miR-149–5p targeted ERP44. The inhibitory impact of DLX6-AS1 overexpression or ERP44 overexpression on proliferation and invasion of trophoblast cells as well as angiogenesis of HUVEC cells was reversed by up-regulating miR-149–5p. We also found that DLX6-AS1 could enhance ERP44 expression by sponging miR-149–5p. Conclusion: DLX6-AS1 inhibited proliferation and invasion of trophoblast cells, and suppressed angiogenesis of HUVEC cells by miR-149–5p/ERP44 pathway. Highlights: DLX6-AS1 overexpression repressed HUVEC angiogenesis. DLX6-AS1 acted as miR-149–5p sponge to regulate ERP44 expression. miR-149–5p rescued the inhibition of ERP44 on trophoblast cells progression. DLX6-AS1 promoted preeclampsia progression by regulating miR-149–5p/ERP44 axis.